Quantification of surface erosion in polymeric insulating material under electrical stress using FTIR, SEM and edge detection. (28th March 2022) - Patel, Chintan; Patel, R.R.
Silicon rubber (polymeric) insulators are extensively preferred in overhead power transmission networks due to their superior performance over the conventional insulators. The surface degradation is an important concern for the insulators as it is organic in nature. The degradation may be caused by a variety of factors like electrical and environmental stresses which will result in the failure of the insulator. This paper discusses the surface erosion study of silicon rubber by applying 3.5 kV voltages (AC and DC with both the polarities) as per IEC 60587. To quantify the surface erosion, Fourier transform infrared (FTIR) and scanning electron microscopy (SEM) have been used. Further, the results are verified by edge detection techniques using Sobel and Prewitt edge detection algorithm. The study revealed that the surface erosion is more with positive DC voltage than AC and negative DC which demands the introduction of appropriate filler materials to enhance the surface properties of the silicon rubber.